Alternatif Penyelesaian Sengketa (APS) Berlandaskan Al-Qur’an dan Al-Hadits - Rakman, Fuad Fatkhu (Sharia Faculty Islamic Economic Law Study Department, 2023)
This study aims to determine the basis for Alternative Dispute Resolution (APS) which includes mediation, negotiation, conciliation, and arbitration in Islamic law taken from the Qur'an and Al-Hadith. The essence of the problem to be revealed in this study is to find models of Dispute Resolution at the time of the Prophet Muhammad SAW. The research method used in this study is a literature study research model by relying on books, articles, journals, and turots as sources of research data. The results of this study found that at the time of the Prophet Muhammad SAW had encountered the practice of resolving disputes through Alternative Dispute Resolution (APS). This is proven by, first, the finding of the arguments for negotiation, mediation, conciliation and arbitration from the Qur'an and Hadith, secondly, the prophet Muhammad SAW negotiated with Suhail Bin 'Amr as a negotiator for the polytheists in the form of a hudaibiyah agreement, the three prophets Muhammad SAW became a mediator in reconciling two people from the ansor circles who were in dispute over material rights, fourth it was found that the prophet Muhammad SAW justified the arbitration carried out by Abu Shuraykh and Sa'ad Bin Muadz.